Early embryonic thermal programming and post-hatch flavonoid (Scutellaria baicalensis) supplementation enhanced immune response markers in broiler chickens - Al Amaz, Sadid; Shahid, Md Ahosanul Haque; Jha, Rajesh; Mishra, Birendra (Frontiers in Veterinary Science, 2025)
IntroductionGenetic selection in broiler chickens has led to increased muscle mass without comparable respiratory and cardiovascular system development, limiting the birds’ capacity to withstand high ambient temperatures and making them vulnerable to heat stress (HS). Early embryonic Thermal Manipulation (TM) has been suggested as an effective and sustainable way to mitigate the adverse effects of HS. This study investigated how these interventions influenced the immune status of broiler chickens exposed to HS.MethodsCobb 500 fertile eggs (n = 600) were incubated according to guidelines. On embryonic day (ED) 12, the eggs were split into two groups: (1) Control, kept at standard temperature until hatch day (ED 21) and (2) Thermal Manipulation (TM), exposed to 38.5°C with 55% humidity for 12 h daily from ED 12 to ED 18. After hatching, chicks were divided into (1) Control, (2) TM, (3) Control under Heat Stress (CHS), (4) TM under Heat Stress (TMHS), (5) Control with Heat Stress and Supplementation (CHSS), and (6) TM with Heat Stress and Supplementation (TMHSS). For the first 21 days, all chicks were raised under normal conditions. From day 22 to day 35, groups CHS, TMHS, CHSS, and TMHSS experienced chronic heat stress (32–33°C for 8 h daily), while the Control and TM groups remained in a thermoneutral environment (22–24°C).Results and discussionTM significantly increased (p < 0.05) AvBD11, IL4, and TLR21 expression in the spleen. TM and baicalein supplementation significantly decreased (p < 0.05) TLR15 expression. In the bursa, TM significantly increased (p < 0.05) IL4 expression. The combination of TM with baicalein significantly increased (p < 0.05) CD3 and decreased (p < 0.05) TLR1 expression. Interestingly, TM alone significantly decreased (p < 0.05) IFNg expression under HS condition. In the thymus, TM significantly decreased (p < 0.05) IL10 and TLR15, while incorporating baicalein with TM decreased (p < 0.05) AvBD6 expression.ConclusionTM improved the immune status of broiler chickens under normal conditions. When combined with baicalein, TM mitigated the negative effects of heat stress by boosting key immune-related gene expression in the spleen, bursa, and thymus.